2012
DOI: 10.1002/jrs.4207
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption mode of neurotensin family peptides onto a colloidal silver surface: SERS studies

Abstract: Kinetensin (KN) and its amino acids 1–8 fragment ([des‐Leu9]KN), neuromedin N (NMN), and xenopsin (XP) and its two analogs (human XP‐1/xenin‐8 and XP‐2) belong to the neurotensin family of peptides and are known to stimulate the growth of human tumors. In this work, we report surface‐enhanced Raman scattering (SERS) studies of these peptides and discuss their structures, orientation, and mode of adsorption onto a colloidal assembly of apparently randomly adhering Ag spheres with diameters of approximately 20 –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It is clear that, with a sufficiently sensitive and selective SERS method, the molecular behavior at the solid/liquid interface and changes in this behavior due to specific modifications (electro-donor substituents at the 2-, 3-, and 4-positions) can be detected in response to these specific regions near or on a metal surface. In addition, the use of SERS techniques assures the enhancement of the scattered signal but also opens new possibilities for the Raman effect, such as the investigation of molecules at a very low concentrations (down to single molecule detection). , This technique is an increasingly powerful spectroscopic tool notably used in the fields of biomedicine and pharmacology, especially in the detection of DNA, detection and identification of neurotransmitters, substrate-receptor modeling, , detection of microorganisms, and monitoring of intracellular drug distribution . Because the SERS spectrum strongly depends on the adsorption mode of the investigated molecule, it provides information about the functional groups of the molecule that are involved in an interaction with the metal substrate, the strength of the interaction, and the molecular fragment’s orientation.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that, with a sufficiently sensitive and selective SERS method, the molecular behavior at the solid/liquid interface and changes in this behavior due to specific modifications (electro-donor substituents at the 2-, 3-, and 4-positions) can be detected in response to these specific regions near or on a metal surface. In addition, the use of SERS techniques assures the enhancement of the scattered signal but also opens new possibilities for the Raman effect, such as the investigation of molecules at a very low concentrations (down to single molecule detection). , This technique is an increasingly powerful spectroscopic tool notably used in the fields of biomedicine and pharmacology, especially in the detection of DNA, detection and identification of neurotransmitters, substrate-receptor modeling, , detection of microorganisms, and monitoring of intracellular drug distribution . Because the SERS spectrum strongly depends on the adsorption mode of the investigated molecule, it provides information about the functional groups of the molecule that are involved in an interaction with the metal substrate, the strength of the interaction, and the molecular fragment’s orientation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that small alternations in both the amino acid composition and tertiary structure, which induce striking biological effects in vitro, were responsible for the observed spectroscopic changes. [80] Sobolewski and coworkers characterized using SERS the adsorption mode of new B2 bradykinin receptor antagonists onto colloidal Ag substrates. The observed spectral changes were analyzed according to the adsorption process and Fouriertransform-Raman spectra.…”
Section: Biomoleculesmentioning
confidence: 99%
“…Proniewicz and coworkers used SERS to study the mode of adsorption of the neurotensin family peptides onto colloidal silver surface. They found that small alternations in both the amino acid composition and tertiary structure, which induce striking biological effects in vitro , were responsible for the observed spectroscopic changes . Sobolewski and coworkers characterized using SERS the adsorption mode of new B2 bradykinin receptor antagonists onto colloidal Ag substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The second, less significant factors concern the chemical effects, in particular the metal-molecule charge-transfer transion and other changes due to the adsorption process [12]. Analysis of the SERS signal (enhancement, wavenumber, and broadness) due to the molecular fragment vibrations of the investigated compound is essential for description of the possible way in which the adsorbate can interact with the surrounding medium [15][16][17][18][19][20]. Thus, SERS is a great tool for low-level detection and analysis, even for the single molecule detection.…”
Section: Introductionmentioning
confidence: 99%